2017
DOI: 10.1038/srep42716
|View full text |Cite
|
Sign up to set email alerts
|

Selection, Characterization and Application of Artificial DNA Aptamer Containing Appended Bases with Sub-nanomolar Affinity for a Salivary Biomarker

Abstract: We have attained a chemically modified DNA aptamer against salivary α-amylase (sAA), which attracts researchers’ attention as a useful biomarker for assessing human psychobiological and social behavioural processes, although high affinity aptamers have not been isolated from a random natural DNA library to date. For the selection, we used the base-appended base (BAB) modification, that is, a modified-base DNA library containing (E)-5-(2-(N-(2-(N6-adeninyl)ethyl))carbamylvinyl)-uracil in place of thymine. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 55 publications
(70 reference statements)
0
46
0
Order By: Relevance
“…structure determination using NMR spectroscopy in solution [99]. This and other reports indicated that NMR guided aptamer optimization could be an optional strategy for aptamer improving binding affinity [100][101][102].…”
Section: Ps2 Walkmentioning
confidence: 74%
“…structure determination using NMR spectroscopy in solution [99]. This and other reports indicated that NMR guided aptamer optimization could be an optional strategy for aptamer improving binding affinity [100][101][102].…”
Section: Ps2 Walkmentioning
confidence: 74%
“…Recently, aptamers have also been proven as hopeful candidates of affinity molecules for target‐specific drug delivery . To date, many aptamers have been successfully selected against a variety of targets and applied on diverse fields . As compared with antibodies, aptamers are showing some unique advantages .…”
Section: Discussionmentioning
confidence: 99%
“…Aptamers are usually screened from a large (10 13 –10 16 ) oligonucleotide (ssDNA or RNA) pool by a technique called systematic evolution of ligands by exponential enrichment (SELEX) in vitro , which contains iterative rounds of selection with amplification steps (Fig. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed steps of the SELEX method are described in Figure . Since SELEX technology was established in 1990 (Ellington & Szostak, ), more than 1,500 aptamers have been identified and exploited for target validation and targeted therapeutics (Minagawa et al, ; Zhou & Rossi, ). Since the first use of aptamers as targeted therapeutics was demonstrated in 1990 by Sullenger, Gallardo, Ungers, and Gilboa (), a number of therapeutic aptamers have made their way into the clinic (Keefe et al, ; Sundaram, Kurniawan, Byrne, & Wower, ).…”
Section: Introductionmentioning
confidence: 99%